The Application of Pregnancy Exercise to the Sleep Quality of Pregnant Women - Khusnul Nikmah; Ida Susila; Rosika Ardhana Apriliari Elsandi (Healthy-Mu Journal, 2023)
The quality of sleep in pregnant women is very important for pregnant women because it is included in the physiological needs that must be met. Changes in the stomach that are getting bigger make it difficult for pregnant women to rest and sleep. Pregnancy exercise is one of the recommended sports during pregnancy because it has the benefit of training breathing and strengthening the pelvic muscles. The purpose of this study was to determine the effect of pregnancy exercise on the sleep quality of pregnant women. This research method is a quantitative study with a Cross Sectional design using a sample of 30 people using the Chi Square test. Obtained a significant value of 0.002 (ρ = <0.005) which means there is an effect of pregnancy exercise on the sleep quality of pregnant women. So it can be concluded that pregnancy exercise activity can be one of the efforts that can be made to improve the quality of sleep in pregnant women.